2015
DOI: 10.1371/journal.pone.0124128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metabolic Syndrome on Mitsugumin 53 Expression and Function

Abstract: Metabolic syndrome is a cluster of risk factors, such as obesity, insulin resistance, and hyperlipidemia that increases the individual’s likelihood of developing cardiovascular diseases. Patients inflicted with metabolic disorders also suffer from tissue repair defect. Mitsugumin 53 (MG53) is a protein essential to cellular membrane repair. It facilitates the nucleation of intracellular vesicles to sites of membrane disruption to create repair patches, contributing to the regenerative capacity of skeletal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 26 publications
8
38
0
Order By: Relevance
“…Several studies have shown that systemic IR can be effectively improved by exercise through reduction of oxidative stress [46, 47]. In the present study, we tested SOD, MDA, GSH-Px, 8-OHdG, and TRIM72 levels in the skeletal muscles of rats in all the groups; the oxidative stress was found increased after long-term feeding with high-fat diet, and, in HFD group, the TRIM72 showed a significant-level promotion on both mRNA and protein expression; this is in accordance with Song et al [8] (published in “ Nature ” 2013), although some publications from different groups showed that HFD treatment does not alter expression of TRIM72 [4853]. We analyzed and inferred the possible reasons: firstly, the differences of the high-fat diet composition: the multiple researchers use the high-fat diet with 45% or more calories from fat or extra cholesterol added.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have shown that systemic IR can be effectively improved by exercise through reduction of oxidative stress [46, 47]. In the present study, we tested SOD, MDA, GSH-Px, 8-OHdG, and TRIM72 levels in the skeletal muscles of rats in all the groups; the oxidative stress was found increased after long-term feeding with high-fat diet, and, in HFD group, the TRIM72 showed a significant-level promotion on both mRNA and protein expression; this is in accordance with Song et al [8] (published in “ Nature ” 2013), although some publications from different groups showed that HFD treatment does not alter expression of TRIM72 [4853]. We analyzed and inferred the possible reasons: firstly, the differences of the high-fat diet composition: the multiple researchers use the high-fat diet with 45% or more calories from fat or extra cholesterol added.…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown that mice with metabolic syndrome induced by 6-month highfat diet (HFD) feeding exhibited a significant increase in serum lipid levels and a significant reduction in circulating MG53 level without change in MG53 expression within skeletal and cardiac muscles. 19 In the present study, we also observed that serum MG53 level was significantly decreased in hyperlipidemic LDLR −/− mice ( Figure 2C).…”
Section: Discussionsupporting
confidence: 80%
“…Little is known on the metabolism of MG53 in vivo. However, it has been shown that serum MG53 levels in mice with metabolic syndrome induced by a 6‐month high‐fat diet were significantly reduced . S‐nitrosylation of MG53 at C144 (cysteine 144) prevented oxidation‐induced degradation of MG53 following oxidative insult, therefore enhancing cardiomyocyte survival .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the cell-molecular mechanisms of Trim proteins, studies have focused on the role of various protein motifs in mediating intracellular signaling events. Similar to other Trim family members, the molecular mechanism of Trim72 has not yet been extensively studied in cardiac fibroblasts [30,31] .…”
Section: Discussionmentioning
confidence: 99%